KombinasiAmpas Tebu dan Serbuk Gergaji Kayu terhadap Kualitas Briket - Ahmed Maulana; Faizah Hamzah; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to get a combination of bagasse and sawdust on the quality of briquettes produced. The method used in this research was Completely Randomized Design, with five treatments and three replications. The treatment used a combination of bagasse and sawdust 0%: 100%, 25%: 75%, 50%: 50%, 75%: 25%, and 100%: 0%. The data obtained were analyzed using Analysis of Variance and continued with Duncan Multiple Range Test at 5% level. The best treatment was briquette 25%: 75% briqutte with water content of 6.3023%, ash content 11.1221%, steam content 22.2391%, carbon content bound to 60.3365%, calorific value 5460 kal.g-1, and fuel 0.0018 g.s -1. Keywords :briquette, bagasse,sawdust.